PREVALENCE OF CYBERBULLYING AND TRADITIONAL BULLYING AND THEIR RELATIONSHIP TO SELFâ€ESTEEM AMONG HEARING-IMPAIRED ADOLESCENTS - Ahmed Hammad, Mohammad; Shaaban Awed, Huda (Humanities & Social Sciences Reviews, 2020)
Purpose: bullying among students with disabilities, especially hearing impairment adolescents is a neglected problem in most Arab countries, including Saudi Arabia. Objective: This study aimed to investigate the prevalence of cyberbullying and traditional bullying and their relationship to selfâ€esteem in adolescent students in southern Saudi Arabia. Methods: Three questionnaires (cyberbullying, traditional bullying, and selfâ€esteem) were used to assess the studied parameters. They were distributed to 81 students with hearing impairment (10th and 12th grade), (Mâ€¯=â€¯18.64, SDâ€¯=â€¯1.06). Main Findings: Findings indicated that 56.4% were exposed to traditional victimization, 52.9% bullied others at school, 44.6% were not exposed to victimization, while 47.1% had not participated. Concerning cyberbullying, 90.5% were not exposed to cyber-victimization, and 94.2% had not participated in cyber-bullying. Males were more exposed to traditional and cyber-victimization than females; besides, they were significantly higher in self-esteem than females. We found a statistically significant correlation between traditional victimization and traditional bully. We also found a statistically significant correlation between self-esteem and both traditional victimization and bully, while no significant correlation between self-esteem and cyber-bully/victims. Novelty/Originality of this study: Additional studies are needed to compare the traditional bullying and cyberbullying, and its relationship to psychological variables among Saudi children with disability and typically developing peers. Moreover, there is an urgent need for evolving prevention and intervention programs to overcome bullying and its negative effects among individual and society.